Working life inequalities: do we need intersectionality?. (28th July 2017) - de los Reyes, Paulina
Abstract: Evidence shows persistent inequalities between women and men regarding working conditions, wage levels, work time, work environment, and career opportunities. At the same time, research results show that inequality in the workplace is not only about gender differences. The specific conditions of oppression built on the simultaneous operation of class, race, and gender relations of power goes beyond the simple dichotomies involved in traditional class analysis or gender studies. Age, nationality, race, sexual preferences, bodily impairment, and class background are crucial factors in the opportunities and obstacles that people face at work. In this article, I discuss how an intersectional perspective can deepen our understanding of the informal hierarchies that create and preserve work life inequalities. Drawing on postcolonial theories and feminist perspectives on labour, I argue that the significance of an intersectional analysis is not primarily about the discrimination mechanisms based on intersecting forms of oppression. Rather, I see the potential of intersectionality in a critical interrogation of the shaping of different perceptions of labour emerging in current models of capitalist accumulation.